Design for manufacture & assembly - Cook, Jerome T.; Koelsch, James R.; Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2005)
Design for manufacture and assembly (DFMA) is a proven design methodology used to optimize part costs and quality, while reducing time-to-market development. This program features an interview with Nicholas Dewhurst of Boothroyd Dewhurst and explains the concepts and use of DFMA in product analysis to understand the drivers of cost, and the interaction of the individual pieces within the product to optimize design, manufacturability, and assembly
Code no : DV05PUB2
Title from title screen
Editor, Jim O'Donnel
Keywords: Design, Industrial; Production engineering; Flexible manufacturing systems